IMPLEMENTATION OF SENIOR STEWARD DUTY AT WHERE’S THE FOOD (WTF) RESTAURANT FOX HOTEL PEKANBARU - Ermalinda "; Mariaty " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The implementation of senior steward duties in the restaurant consists of: 1) Briefing, 2) Making Request to Purchase Goods, 3) Inventory, 4) Making Schedule for Cleaning Tools, 5) Controlling. This research aims: to determine the implementation of senior steward duties at Where’s The Food (WTF) Fox Hotel restaurant. This research used a qualitative descriptive method, with research subjects consisting of steward employee, executive chef, and Food and Beverage Manager (FBM). Data collection is done by means of observation, interviews, and documentation. Data analysis in this research is data reduction, data presentation, and drawing conclusions. And the results of the research show that the implementation of senior steward duties in the Where’s The Food (WTF) restaurant such as briefings with execurive chef, making Store Request (SR) for work items such as cleaning supplies and work equipment, implementing monthly and annual inventory, and making jobdesc daily, weekly, and monthly steward employees are in accordance with the standards. Only controlling was not in accordance with the predetermined standards. Keywords: Implementation of Senior Steward Duties, Job Description